The Correlation between Knowledge and Habit of Handwashing with Soap on Students of Primary School 101893 Bangun Rejo - Rahma Yunita Amar (International Archives of Medical Sciences and Public Health, 2021)
Hand washing is a preventative and curative measure that has evolved into clean and healthy living behavior programs in schools. Hand washing with soap is one of the sanitation measures that humans use to clean their hands and fingers with water and soap in order to stay clean and break the germ chain. Hand washing with soap is also referred to as a preventative measure. This is because the hands frequently act as carriers of germs. The purpose of this study is to ascertain the relationship between knowledge and the habit of hand washing with soap among students at primary school 101893 Bangun Rejo in Tanjung Morawa District. This is an analytical study that takes a quantitative approach and employs a cross-sectional research design. The population was comprised of all 487 students enrolled in primary school 101893 Bangun Rejo. This study enrolled students in grades IV and V, totaling up to 70 students. This sampling technique employs a method known as cluster random sampling. Data were gathered through the distribution of questionnaires and their completion by students. Techniques for data analysis utilizing the Chi-square test. The findings indicated that students lacked knowledge regarding proper hand washing behavior when using soap (31.4 percent ). Handwashing with soap is insufficient (34.3 percent ). The study's conclusion indicates that there is a statistically significant relationship between knowledge and behavior regarding hand washing with soap (p = 0.000). To increase knowledge and practice of proper hand washing, schools must provide facilities that promote clean and healthy living behaviors, particularly hand washing with soap, as well as health education about the importance of continuous hand washing..